Diskriminasi Kaum Minoritas dalam Novel Maryam Karya Okky Madasari: Kajian Sosiologi Sastra - Sintya Nur Alifah; Haryanti, Novi Diah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This study will discuss the discrimination of minorities, the discrimination referred to in this study is to provide a picture of the oppressed minority community, namely the Ahmadiyah who live in the area. The purpose of this study is to provide an overview of the Ahmadiyya community who live in concerns and disapproval of the people outside the Ahmadiyah for the residence of these minorities, resulting in rebellion, arson, and also expulsion. In this study, the author uses a method to make it easier to analyze the object of his research. This study uses a descriptive qualitative methodological approach and a theoretical approach to sociology of literature, namely a literary approach that focuses more on general social issues. The results of this study will explore more deeply about the discrimination of minorities in society contained in the novel Maryam, and also discuss about a conflict between members of the community that we can see from this novel.